Assessment of Turbulence Models on a Backward Facing Step Flow Using OpenFOAM®. Issue 4 (August 2020) - Singh, Anugya; Aravind, S; Srinadhi, K; Kannan, B T
Abstract: Studies on turbulent inlet flows have a wide variety of applications, Backward Facing Step (BFS) facilitates this study. The phenomena of flow separation occur due to an abrupt change in geometry, causing the creation of a re-circulation zone and a flow reattachment point. The present numerical study focuses on the assessment of different turbulence models. The flow velocity is in the turbulent region characterized by the Re=7000. Steady State Reynolds Averaged Navier Stokes equations are solved along with various turbulence models using OpenFOAM® which is an open-source Computational Continuum Mechanics toolbox for conducting numerical simulations. The simulated data is processed using Paraview and the assessment of the turbulence models is performed via quantitative (reattachment length) and qualitative (Line Integral Convolution visualizations) methods.